Antioxidant and antihyperglycemic activity of Sophora alopecuroides seed on streptozotocin-nicotinamide induced diabetic rats / Abdulwali Ablat - Abdulwali , Ablat (2012)
Sophora alopecuroides seed (SAS) was extracted with chloroform, ethanol and distilled water. The TLC result showed the presence of alkaloids in all of the extracts and the total alkaloid contents was 7.56%. The alkaloids were separated and identified with Q-TQF MS with known reference standard and were found that Sophora alopecuroides seed contained alkaloids namely sophocarpine, matrine, baptifoline, oxysophocarpine, oxymatrine, sophocarpine dimer, oxysophocarpine dimer, oxymatrine dimer and sophoranol-N-oxide dimer. The in vitro bioassays were performed to determine the antioxidant activity and glycogen phosphorylase enzyme inhibition activity of Sophora alopecuroides seed in ethanol and water extracts. In all of the bioassays, ethanol extract had showed highest activities. In DPPH assay the IC50 value of ethanol extract was 155.33 ± 0.06 μg/ml while in FRAP assay the IC50 value of ethanol extract was 9.71 ± 0.02 μg/ml. In GPa enzyme assay the IC50 of ethanol Sophora alopecuroides seed extract was 581.61 μg/ml. Acute toxicity of ethanol Sophora alopecuroides seed extract was tested at increasing dose level in non-diabetic rats and no toxic effects were observed in male rats at a dose of 5 g/kg body weight. The ethanol Sophora alopecuroides seed extract at the dose of 500 mg/kg was capable of decreasing the glycemia of non-diabetic rats during an oral glucose tolerance test (OGTT). The treatment with SAS at the dose of 500 mg/kg to the diabetic rats for 28 days decreased fasting blood glucose levels significantly compared to the 0th day. The 95% ethanol SAS extract at the dose of 250 mg/kg and 500 mg/kg body weight significantly (*P < 0.05) decreased serum triglycerides and total cholesterol levels, and increased serum HDL levels compared to the diabetic control. Therefore, these results validate the traditional use of Sophora alopecuroides seed as an antidiabetic remedy.